2009
DOI: 10.1021/jp906082u
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Excitation of Molecular Adsorbates on Flash-Heated Gold Surfaces

Abstract: An ultrafast flash-thermal conductance technique is used to study energy transfer from a flash-heated polycrystalline Au(111) surface to adsorbed thiolate self-assembled monolayers (SAMs). The focus is on understanding energy transfer processes to parts of SAM molecules situated within a few carbon atoms of the Au surface, by probing specific SAM functional groups with vibrational sum-frequency generation (SFG) spectroscopy. The SFG intensity drop after flash-heating for benzenethiol (BT) CH-stretch transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
47
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 41 publications
0
47
0
Order By: Relevance
“…Advances in experimental techniques at nanoscale shift focus of research in molecular electronics [1][2][3][4][5] from ballistic transport 6,7,99 to inelastic effects 9,10,12,93 (and closely related energy transfer processes [13][14][15][16][17][18] ), to noise characteristics [19][20][21] and optical response [22][23][24][25][26] in current carrying junctions. Recent spin-transport experiments 27,28 demostrated potential possibility of using organic molecules to construct molecular spin devices, indicating the emergence of molecular spintronics [30][31][32][33][34][35] (see Ref.…”
mentioning
confidence: 99%
“…Advances in experimental techniques at nanoscale shift focus of research in molecular electronics [1][2][3][4][5] from ballistic transport 6,7,99 to inelastic effects 9,10,12,93 (and closely related energy transfer processes [13][14][15][16][17][18] ), to noise characteristics [19][20][21] and optical response [22][23][24][25][26] in current carrying junctions. Recent spin-transport experiments 27,28 demostrated potential possibility of using organic molecules to construct molecular spin devices, indicating the emergence of molecular spintronics [30][31][32][33][34][35] (see Ref.…”
mentioning
confidence: 99%
“…5 We did not try to compensate for spectral chirp, which was less than 1 ps. The white light was split into signal and reference beams which were focused to 100 lm and were incident at 30 .…”
Section: E Reflectance Measurementsmentioning
confidence: 99%
“…5 We showed it was possible to use SFG to probe hot electron-and phonon-excited vibrations at multiple locations on the adsorbate molecules, 2 and it was shown that the hot electrons excited atomic groups most effectively if they were no farther than 4-5 carbon atoms away from the surface. 5 Flash-heating of Au surfaces by short pulses of light has been studied extensively over the past 25 years using transient reflectance probes. 6,7 Reflectance transients are sensitive to changes in the conduction electron densities caused by optical excitation and by heat.…”
mentioning
confidence: 99%
See 2 more Smart Citations